Analysis of Mathematics Literacy of Students of Mathematics Education Department Viewed from Process Components - Rusmining, Rusmining (Department of Mathematics, Universitas Negeri Semarang, 2017)
The PISA study measures the mathematical literacy of reasoning, arguing, and problem-solving skills. The research question is how the ability of mathematics literacy of mathematics education students viewed from process components. This research uses qualitative approach using documentation, observation, and interview. The results showed that 60 students or 100% were below level 1, with a score of less than 358. In the process component, communication skills obtained an average score of 3.29. Mathematising got an average score of 2.71. Representation got an average score of 3.08. Reasoning and argument got an average score of 2.54. Devising strategies for solving problems got an average score of 2.83. Using symbolic, formal and technical language and operation earned an average score of 3.16. Ability to use mathematics tools get an average score of 3.16. Based on the results of the study concluded that the literacy ability of mathematics education students viewed from the components of the process is very low.